Fumonisin B1 induces hepatotoxicity in mice through the activation of oxidative stress, apoptosis and fibrosis. (June 2022) - Cao, Changyu; Xian, Runxi; Lin, Fanghui; Li, Xinting; Li, Xiaowen; Qiang, Fu; Li, Xinran
Abstract: Fumonisin B1 (FB1) is a harmful environmental pollutant that induces hepatotoxicity, but the mechanism is still poorly understood. Therefore, the aim of this work was to investigate the effects of FB1 on the liver of mice and discover the underlying molecular mechanisms. A total of 40 male mice were exposed to 0 or 5 mg/kg FB1 for 42 days, and then, they were sacrificed, and the liver and blood were collected. Besides, AML12 cells were exposed to FB1. Biochemical and liver related indexes as well morphological changes, redox, apoptosis and fibrosis related markers were measured in liver and AML12 cells. The results showed that the liver function and biochemical indexes in the blood were changes, and the histopathological analysis indicated that FB1 exposure caused hepatic sinusoid atrophy, hemosiderosis, hepatocyte steatosis and fibrosis, finally inducing liver injury. Notably, a significant increase in the intracellular antioxidant enzymes SOD1, SOD2, NF-κB (p65), H2 O2 and NO was found in FB1 exposed AML12 cells and liver tissues. In addition, TUNEL staining showed many apoptotic cells, and western blotting revealed a significant increase in the pro-apoptosis proteins. FB1 also induced liver fibrosis by triggering TGF-β1/α-SMA/collagen/MMP signaling in the hepatocytes. Our results provide a novel explanation of the toxicological mechanism of action of FB1, which provoked oxidative stress, apoptosis and fibrosis in mice liver. Graphical abstract: Image 1 Highlights: Fumonisin B1 induces histological alterations in liver and AML12 cells of mice. Fumonisin B1 induces oxidative stress of mice. Fumonisin B1 induces apoptosis of mice. Fumonisin B1 induces fibrosis of mice.